R&D dynamics with asymmetric efficiency - Ferreira, Miguel (2016)
We consider an R&D investment function in a Cournot duopoly competition model inspired in the logistic equation. We study the economical effects resulting from the firms having different R&D efficiencies. We present three cases: (1) both firms are efficient and have the same degree of efficiency; (2) both firms are less efficient and have the same degree of efficiency; (3) firms are asymmetric in terms of the efficiency of their R&D investment programs. We study the myopic dynamics on the production costs obtained from investing the Nash investment equilibria.